2009
DOI: 10.1111/j.1442-9993.2009.01989.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a single burn event on the aquatic invertebrates in artesian springs

Abstract: Fire can often occur in aquatic ecosystems, which may affect aquatic invertebrates. Despite the importance of aquatic invertebrates to ecosystem function, the effect of fire on these environments has been little studied.We studied the effects of fire on aquatic invertebrates in artesian springs in the arid zone of South Australia. Artesian springs are a unique and threatened ecosystem, containing several rare and endemic species. Evidence suggests these wetlands were routinely burnt by indigenous Aboriginal pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…These habitat alterations and trophic changes concur with most studies dealing with wildfires and aquatic systems (Lewis et al, 2014;Minshall et al, 2001). This fast increase in shredder abundance has also been observed in other lentic habitats (Lewis et al, 2014;Munro, Kovac, Niejalke, & Cunningham, 2009;Scrimgeour et al, 2001). However, these changes did not affect colonisation by active dispersers and instead seemed mainly to alter the available resources.…”
Section: Community Composition and Functional Traitssupporting
confidence: 87%
See 1 more Smart Citation
“…These habitat alterations and trophic changes concur with most studies dealing with wildfires and aquatic systems (Lewis et al, 2014;Minshall et al, 2001). This fast increase in shredder abundance has also been observed in other lentic habitats (Lewis et al, 2014;Munro, Kovac, Niejalke, & Cunningham, 2009;Scrimgeour et al, 2001). However, these changes did not affect colonisation by active dispersers and instead seemed mainly to alter the available resources.…”
Section: Community Composition and Functional Traitssupporting
confidence: 87%
“…However, we found that as the hydroperiod commenced, within the first 2-4 months after fire in burned ponds, shredders had higher abundances. This fast increase in shredder abundance has also been observed in other lentic habitats (Lewis et al, 2014;Munro, Kovac, Niejalke, & Cunningham, 2009;Scrimgeour et al, 2001). This rapid rise and subsequent decrease F I G U R E 6 Changes in abundance of piercers (a), scrapers (b), and shredders (c) along the hydroperiod for the high-intensity ponds (black circles with solid line), low-intensity ponds (grey triangles with dashed line) and unburned ponds (white squares with dotted line).…”
Section: Community Composition and Functional Traitssupporting
confidence: 76%
“…Post‐fire recovery of invertebrate communities can occur via multiple mechanisms including survival in situ , recolonisation by dispersal or reproduction from egg banks (e.g. Munro et al ., 2009; Robson et al ., 2018). However, without a better understanding of the fundamental ecology of invertebrate taxa and how these mechanisms of resilience support post‐fire recovery over extended spatial scales, our ability to predict and manage for recovery is limited.…”
Section: Relevance Of Available Evidence To Conservation Policymentioning
confidence: 99%
“…In GAB springs, the majority of endemic species are invertebrates with highly restricted ranges, specific habitat requirements (Ponder et al 1989;Rossini et al, 2017), and exposure to the same threats as better-protected species like the fishes (e.g. predation by invasive species (Clifford et al, 2013), habitat degradation associated with disturbance (Kovac & Mackay, 2009;Munro et al, 2009). If we are to maintain biodiversity in this system, more attention needs to be afforded to endemic invertebrates and their conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to collect data have generally been idiosyncratic; published research has employed different methods with effort focussed on particular regions and taxa (Table 3-1). Targeted studies of diversity or abundance are rare, meaning rapid methods with no implicit spatial component within the spring are the norm (Munro et al, 2009) (Table 3-1). Relatively few studies use 'coring' (Table 3-1), although this method is common in other submersed vegetated environments (e.g.…”
Section: Introductionmentioning
confidence: 99%